Risk prediction of in-hospital mortality in patients with venoarterial extracorporeal membrane oxygenation for cardiopulmonary support: The ECMO-ACCEPTS score - Becher, Peter Moritz; Twerenbold, Raphael; Schrage, Benedikt; Schmack, Bastian; Sinning, Christoph R.; Fluschnik, Nina; Schwarzl, Michael; Waldeyer, Christoph; Seiffert, Moritz; Clemmensen, Peter; Neumann, Johannes T.; Bernhardt, Alexander M.; et al. (Journal of critical care, 2020)
Purpose - Venoarterial extracorporeal membrane oxygenation (VA-ECMO) is an increasingly used treatment option for patients in need of mechanical cardiopulmonary support, while available outcome data is limited. The aim of this study was to identify predictors for 30-day in-hospital mortality. - Material and methods - We analyzed baseline characteristics and outcomes of 8351 VA-ECMO procedures performed in Germany from 2007 to 2015. Using a multivariable model, we identified the ten most important variables to allow for prediction of 30-day in-hospital mortality. Based on these variables, we created a mortality prediction score (ECMO-ACCEPTS score) to enhance decision making in patients considered for or treated with VA-ECMO support. - Results - Of 8351 patients (71.7% male) 3567 had prior CPR. Mean age was 62 years in the present cohort. The overall 30-day in-hospital mortality was 61%. The ECMO-ACCEPTS score, derived among randomly selected 4175 patients, included ten independent predictors for in-hospital mortality. Internal validation in the remaining 4176 patients confirmed strong differentiation between low and high risk of 30-day in-hospital mortality (r = 0.97 for correlation of predicted with observed mortality, p < .001). - Conclusions - The ECMO-ACCEPTS score might help clinicians to improve risk prediction among VA-ECMO patients for refractory cardiogenic shock.
Available online 13 December 2019
Gesehen am 07.04.2020